Design Architecture for IMPlayer as a Tool for Supporting Visual Education Presentation - Asnawi, Rustam; Wan Ahmad, Wan Fatimah; Awang Rambli, Dayang Rohaya (Springer-Verlag, 2009)
Presentation of teaching-learning materials in various visual media forms is immensely necessary and important for educators and students in visual education. Most often these materials which include videos, audios, and images exist in numerous file formats indicating the needs for different types of multimedia applications to run them. Thus, utilizing various combinations of many file formats during a presentation implies the needs to have the necessary media players and be familiar with all of them. This can be very awkward for a presenter especially when switching between players during a presentation. In this paper, an integrated player (IMPlayer) which allows user to run multiple media in a single application is proposed as a solution. Basically, the application provides an interface that allows easy access to various players. The design architecture which supports multiplayer mode and dual-view features is presented. Example uses of the tool to support visual education presentation are also described.